THE POST-TRAUMATIC GROWTH OF VIOLET MARKEY AFTER EXPERIENCING POST-TRAUMATIC STRESS DISORDER IN ALL THE BRIGHT PLACES NOVEL - Annisa Ika Yuliana; Destary Praptawati (Universitas Duta Bangsa Surakarta, 2025)
Traumatic events that pose a threat to one's life can cause PTSD. Positive changes that a person experiences after going through trauma are referred as PTG. Violet Markey, as the main character in All the Bright Places Novel, experienced post-traumatic stress disorder. This study aims to analyze the domains of post-traumatic growth that were achieved after successfully going through PTSD symptoms. This study applies post-traumatic stress disorder theory by Gleen R. Schiraldi and Richard Tedeschi and Lawrence Calhoun’s post-traumatic growth theory. This study analyzed the data which included dialogue, sentences, and phrases using qualitative research method. The process of collecting data involves multiple steps, such as reading the novel, identifying, classifying, and reducing the data. The findings of this study portrayed that the symptoms of PTSD in Violet Markey are re-experiencing, arousal, and avoidance. Furthermore, Violet experienced personal strength, relating to other, new possibilities, appreciation of life, and spiritual change as a result of post-traumatic growth. It can be concluded that a person can achieve post-traumatic growth after dealing with the symptoms of PTSD.